Determination of Optimal Freshwater Prawn Farming Site Locations using GIS and Multicriteria Evaluation - Mustafa, Firuza Begham; Bwadi, Benjamin Ezekiel (Coastal Education and Research Foundation, 2018)
Mustafa, F.-B. and Bwadi, B.E., 2018. Determination of optimal freshwater prawn farming site locations using GIS and multicriteria evaluation. In: Ashraf, M.A. and Chowdhury, A.J.K. (eds.), Coastal Ecosystem Responses to Human and Climatic Changes throughout Asia. Site suitability selection is an essential condition for attaining maximum use of any land resources. Inadequate information about factors that influence the production of giant freshwater prawn has contributed to the low production in many regions. This study was to determine the best giant freshwater prawn farming site using the multicriteria evaluation (MCE) and GIS methods in the Negeri Sembilan state of Peninsular Malaysia. The analytic hierarchy process (AHP) pairwise comparison matrix was used to determine the weights for the physicochemical factors of water, soil, and infrastructure used in the analysis. The factor maps were generated through the data stored in the ArcGIS 10.1 environment. The present land-use map of the area was created from the shape-file map of the prawn farming areas. The results revealed that 18% of the area presently being used was most suitable areas, 49% was moderately suitable, and 33% was not suitable. The potential area for prawn farming is 441,421.56 ha; of which, only 441.80 ha (1%) have been under farming. The results of model verification showed that the suitability map was 100% consistent with the current farms in the study area when compared. GIS and AHP methodologies were found to be effective for site suitability selection for prawn farming. The results of the study can be useful for decision making about prawn farming in the study area.